Malignant eccrine spiradenoma on the lateral margin of nose as an infrequent localization - Bercin Sami; Kutluhan Ahmet; Metin Ahmet; Suren Dinc (Wolters Kluwer Medknow Publications, 2009)
Malignant eccrine spiradenomas are exceedingly rare tumors. They can arise from a preexisting eccrine spiradenoma or occur as a primary malignant tumor. Clinical features of these tumors may include a history of enlargement in a previously stable lesion. Tumor can be of low or high grade. Low-grade malignant eccrine spiradenoma has a better prognosis. We present a malignant eccrine spiradenoma arising from a preexisting eccrine spiradenoma, which has an infrequent localization between lateral edge of nose and medial canthus.